Delayed diagnosis and racial bias in children with genetic conditions. Issue 4 (17th January 2022) - Omorodion, Jacklyn; Dowsett, Leah; Clark, Robin D.; Fraser, Jamie; Abu‐El‐Haija, Aya; Strong, Alanna; Wojcik, Monica H.; Bryant, Allison S.; Gold, Nina B.
Abstract: As more therapeutics for genetic conditions become available, the need for timely and equitable genetic diagnosis has become urgent. Using clinical cases, we consider the health system‐, provider‐, and patient‐level factors that contribute to the delayed diagnosis of genetic conditions in pediatric patients from minority populations, leading to health disparities between racial groups. We then provide suggestions to address these factors, with the aim of improving minority health and access to genetic care for all children.